Pengembangan Perangkat Pembelajaran IPA SD/MI Menggunakan Inkuiri Terbimbing untuk Melatih Keterampilan Berpikir Kritis Siswa pada Materi Struktur Tubuh - Abdul Gani (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2018)
This research aims to bring out science teaching material by using guided inquiry which is feasible to facilitate student’s critical thinking skill. The development used 4D model and have been implementation in four year’s class of MI Hidayatussibyan on first semester 2017/2018 with One-Group Pretes-Posttest Design. Data were collected through validation, observation, test, and questionnaire method. The data was analized by using quantitative and qualitative descriptive analysis. Results showed: 1) the teaching material developed which involve syllabus, lesson plan, textbook, worksheet, conceptual understanding test and critical thinking skill test are in valid category; 2) the material are categorized as practice where lesson plan was carried out, and student’s activity followed stages of guide inquiry model; and 3) they are effective where: (a) the increasing of conceptual understanding of students can be observed by the increasing of classical completeness from 46,46 to 87,15; (b) critical thinking skill went up with n-gain of high category (0,52); and (c) student’s respond to guided inquiry instruction is in good category. Therefore, the material is feasible to facilitate student’s critical thinking skill.